The Effect of Dehydration Levels on the Training Volume of Special Class Pencak Silat Athletes in Semarang City - Shelvia Rahmawati; Sugiarto (Universitas Negeri Semarang, 2025)
Optimal body hydration is essential in supporting physical performance and training effectiveness, especially in sports such as pencak silat, which demand strength, agility, and endurance. Fluid imbalance, or dehydration, can impair muscle function, accelerate fatigue, and hinder the body's ability to adapt to training loads. This issue is often overlooked, particularly among young athletes who may lack awareness of proper hydration practices. This study aims to examine the effect of dehydration level on the training volume of pencak silat athletes enrolled in the Special Sports Class (KKO) in Semarang City. Dehydration was assessed by observing urine color using a standard hydration scale, while training volume was measured through heart rate calculations based on the Karvonen formula. Data were analyzed using simple linear regression and Pearson correlation. The results revealed a significant negative relationship between dehydration level and training volume. Higher dehydration levels were associated with lower training volume among athletes. These findings emphasize the importance of hydration monitoring in youth athlete training systems to ensure effective performance development and reduce the risk of fatigue or injury.